2009
DOI: 10.1103/physrevb.79.214203
|View full text |Cite
|
Sign up to set email alerts
|

Collective dynamics and molecular interactions in liquidCO2by inelastic neutron scattering and computer simulations

Abstract: We report an inelastic neutron scattering determination of the dynamic structure factor of liquid carbon dioxide in the wave-vector range 3 Ͻ Q Ͻ 17 nm −1 and molecular dynamics simulations performed using several site-site intermolecular interaction models. The comparison of neutron and simulation dynamical spectra allows effective model-potential selection. The good performance of some of the CO 2 anisotropic interaction models enables a thorough investigation of the collective properties, taking full advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
(61 reference statements)
0
15
1
Order By: Relevance
“…This phenomenon is one of the causes of the bending upwards of the dispersion curve, whose overall shape is however determined by a number of facts [35]. In particular, the growth of the damping z s with Q tends instead to reduce the excitation frequency up to the point where the acoustic oscillations are brought into the overdamping condition causing the above mentioned propagation gap [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is one of the causes of the bending upwards of the dispersion curve, whose overall shape is however determined by a number of facts [35]. In particular, the growth of the damping z s with Q tends instead to reduce the excitation frequency up to the point where the acoustic oscillations are brought into the overdamping condition causing the above mentioned propagation gap [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we analyze spectra obtained by molecular dynamics simulations, which usually present the further advantage of being calculated in broad frequency ranges. However, the compatibility of simulations with available experimental data has been demonstrated [21,22] as a preliminary, mandatory task to be carried out before confidently resorting to simulated data.…”
Section: Applicationsmentioning
confidence: 97%
“…CO 2 can be considered as a classical fluid, so that the expansion in Lorentzian functions can be applied directly to the structure factor, which for a homogeneous and isotropic fluid depends only on the magnitude k of the wave vector k. In Ref. [22] it was shown that the spectrum is well described if the continued fraction is truncated at the level of the second-order memory function and a viscoelastic modeling for the latter is assumed, which is known to give rise to a four-Lorentzian spectrum [17]. In the whole k range, with the exception of an interval around the position of the main peak of the static structure factor S(k), two of the four lines are characterized by complex eigenfrequencies and correspond to the excitation of acoustic modes.…”
Section: B the Dynamic Structure Factor Of Liquid Comentioning
confidence: 99%
See 2 more Smart Citations